Market Sensing Capabilities, Inovasi Produk sebagai Peningkatan Competitive Advantage pada UMKM Produk Pangan Olahan Terkemas Kecamatan Tutur - Nuraeni, Nuraeni; Santia, Devta Argu (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
The International Monetary Fund (IMF) has notified all countries that one-third of the globaleconomy will experience an economic recession this year. The global economic recession is expected tooccur due to the slowing economies of the United States (US), the European Union, and China. In facing aneconomic recession, there is one economic actor that is expected to be the savior of the country's economy,namely Micro, Small and Medium Enterprises (MSMEs). MSMEs of oilahan teirkeimas food products areMSMEs that produce processed products from plantations, agriculture, and livestock. This is verysupportive of the Tutur District area which is rich in crops and livestock, so that packaged processed foodproducts MSMEs have their own competitiveness and value. This research was conducted to determine theinfluence of market sensing capabilities, product innovation, and competitive advantage. The sample in thisstudy is Packaged Processed Food Products MSMEs in Tutur District with a total of 81 MSME units. Thisresearch also uses the WarpPLS 7.0 analysis tool, by looking at the outer model and inner model values.